SUSTAINABLE CURRICULUM IN TVET - Lasonen, Johanna (Journal of Technical Education and Training, 2010)
In some European countries, students receive vocationally oriented education as early as at the age of 12. The students transfer to lower secondary school at the age of 10-13, with the youngest entrants found in Germany and Austria and the oldest ones, being at the age of 16, in the Nordic countries. The most thoroughly school-based vocational upper secondary education is provided in Finland, Sweden, Spain, Greece and Portugal. The highest proportion of vocational training delivered at the workplace is to be found in Austria (a little less than half) and the Netherlands (a third), that of training combining the workplace and school in Denmark, Germany, France and the Netherlands. Curriculum denotes the formal specification of what is taught and learnt in educational or training establishments. Curricula are formally specified in such learning and teaching entities as units, courses, clusters, sequences and other specifications. Levels of curricula vary from national to student ones, and types of curricula differ from intended to learned syllabi. The traditions of curriculum vary according to national contexts and to historical periods. Curriculum development in TVET is approached from a broad technological knowledge, activity-oriented theories of learning and from the concept of vocation (Beruf). Ethics of sustainable development gives a global and future perspective to education and training. The first two chapters illustrate the global, regional and national policy context of curriculum in TVET followed by a historical discussion about a curriculum theory and didactics. Then the learning theories focus on work-based learning issues and an activity approach. Next the ethics and implementation of education for sustainable development is analysed. Finally a window to the future is opened by a national practice of workforce anticipation.